2020
DOI: 10.3390/cancers12020387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Andrographolide on Intracellular pH Regulation, Cellular Migration, and Apoptosis in Human Cervical Cancer Cells (Running Tittle: Effects of Andrographolide on pH Regulators and Apoptosis in Cervical Cancer)

Abstract: Cancer cells have been characterized with alkaline intracellular pH (pHi) values (≥7.2) to enable cancer proliferation, migration, and progression. The aim of the present study was to explore the concentration-dependent effects of Andrographolide, an active diterpenoid compound of herb Andrographis paniculata, on Na+/H+ exchanger isoform 1 (NHE1), cellular migration and apoptosis in human cervical cancer cells (HeLa). The pHi was detected by microspectrofluorometry method, and intracellular acidification was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…An experiment by Chiang et al demonstrated that EGF is involved in the regulation of NHE1 expression via the PI3K signaling pathway in cervical cancer (91), and NHE1 can also interact with the actin-related protein ezrin to reconstitute the cytoskeleton and stimulate the migration and invasion of cervical cancer cells. It was also reported that Andrographolide regulates the expression of apoptotic proteins to induce cells apoptosis, and concentration-dependently decreases pHi by decreasing the activity of NHE1/V-ATPase and the expression of NHE1 in HeLa cells; thus, Andrographolide may represent a promising novel agent in the treatment of cervical cancer in the clinical setting (92). In addition, NHE has also been found to be involved in the regulation of uterine fluid pH (Fig.…”
Section: Nhe1 and Cervical Cancermentioning
confidence: 85%
“…An experiment by Chiang et al demonstrated that EGF is involved in the regulation of NHE1 expression via the PI3K signaling pathway in cervical cancer (91), and NHE1 can also interact with the actin-related protein ezrin to reconstitute the cytoskeleton and stimulate the migration and invasion of cervical cancer cells. It was also reported that Andrographolide regulates the expression of apoptotic proteins to induce cells apoptosis, and concentration-dependently decreases pHi by decreasing the activity of NHE1/V-ATPase and the expression of NHE1 in HeLa cells; thus, Andrographolide may represent a promising novel agent in the treatment of cervical cancer in the clinical setting (92). In addition, NHE has also been found to be involved in the regulation of uterine fluid pH (Fig.…”
Section: Nhe1 and Cervical Cancermentioning
confidence: 85%
“…Modern science is focusing on validating the traditional claims of this plant through systemic investigations. Different extracts (i.e., acetone, chloroform, ethanol, hexane, methanolic or aqueous extract) and isolated pure metabolites from A. paniculata have been investigated for pharmacological properties, for example, antibacterial, antiviral, antifungal, antiparasitic, choleretic, hypocholesterolemia, anti-inflammatory, anti-hyperglycemic, hepatoprotective, anticancer, immunomodulatory, cardiovascular, antihyperlipidemic, emollient, anti-snake venom, anti-platelet aggregation, anti-fertility, carminative, and antipyretic properties at in vitro and in vivo conditions [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the above non‐solid tumors, According to Loh et al, andrographolide inhibited cell survival and migration in human cervical cancer cells. This study showed therapeutic effects in treating cervical cancer may occur in andrographolide 256 . According to increasing evidence, Andrographolide has been investigated as a leading component in cancer treatment.…”
Section: Andrographolide In Cancersmentioning
confidence: 68%
“…This study showed therapeutic effects in treating cervical cancer may occur in andrographolide. 256 According to increasing evidence, Andrographolide has been investigated as a leading component in cancer treatment. There are still several obstacles to better promoting andrographolide and its analogs as cancer therapy agents.…”
Section: Other Cancersmentioning
confidence: 99%